(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
The birth of the “Rivista di Studi e Ricerche sulla Criminalità Organizzata” represents a new step in the journey began by the University of Milan Studies to build a specific disciplinary field dedicated to the mafia phenomenon. It moves from the consciousness that knowledge is a real productive force in the fight against the mafia phenomenon. This consciousness is an indispensable resource for the Italian democracy, that the university must cooperate to generate and regenerate, welcoming and interpreting the issues and the sensitivity coming from the new generations. The constitution of a “interdisciplinary and multidisciplinary” discipline, the rediscovery of the finalities ed of the energy of the academic knowledge, the exploitation of young talents, will be the principle criteria to evaluate in the next few years the vitality of the new review.